Ascetyczny wymiar „ćwiczenia się w śmierci” w Drabinie raju św. Jana Klimaka - Jasiewicz, Arkadiusz (Verbum Vitae, 2013)
‘The monk’s Home is his ‘tomb before the tomb… For no one leaves the tomb until the general resurrection. But if some depart, know that they have died’. The monk lives as though dead on the earth yet. Climacus highlights the profound importance of understanding the practices like ‘remembrance of death’ and metaphorical usage of ‘death’ for interpreting the ideals and tools of Christian asceticism. For John Climacus, the event and concept of death provide the organizing logic for ascetic life – principles according to which the monk can make progress by guarding his heart, by repentance and cry, prayer, struggle, and humility.